2015
DOI: 10.1371/journal.pone.0133979
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Inactivated Human Skin Using High Hydrostatic Pressurization for Full-Thickness Skin Reconstruction

Abstract: We have reported that high-hydrostatic-pressure (HHP) technology is safe and useful for producing various kinds of decellularized tissue. However, the preparation of decellularized or inactivated skin using HHP has not been reported. The objective of this study was thus to prepare inactivated skin from human skin using HHP, and to explore the appropriate conditions of pressurization to inactivate skin that can be used for skin reconstruction. Human skin samples of 8 mm in diameter were packed in bags filled wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 30 publications
5
43
0
Order By: Relevance
“…In recent years, EDX/SEM systems have become more and more attractive for the nanoscale investigation of biological structures in various medical fields (pathology of the heart [6,7], kidney [8,9], skin [10,11], and hair [12,13,14]).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, EDX/SEM systems have become more and more attractive for the nanoscale investigation of biological structures in various medical fields (pathology of the heart [6,7], kidney [8,9], skin [10,11], and hair [12,13,14]).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that HHP at 200 MPa for 10 min can inactivate mammalian cells, skin and melanocytic nevus tissue; however, those were not inactivated at HHP lower than 150 MPa [Mahara et al, 2014;Liem et al, 2015;Morimoto et al, 2015]. Therefore, we choose pressures of 100 and 200 MPa in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that HHP at 200 MPa for 10 min can inactivate mammalian cells and that it is capable of inactivating skin and melanocytic nevus tissue in light brown to black patches or plaques that contain nevus cells [Mahara et al, 2014;Jinno et al, 2015;Liem et al, 2015;Morimoto et al, 2015]. Giant congenital melanocytic nevi (GCMN), which are defined as nevi of more than 20 cm in diameter [Watt et al, 2004;Tannous et al, 2005;Zaal et al, 2005;Turkmen et al, 2010;Arad and Zuker, 2014], are reported to occur in approximately 1 in 20,000 newborns and have the risk of transforming into malignant melanomas in approximately 1-3% of individuals with GCMN [Tannous et al, 2005;Zaal et al, 2005;Arad and Zuker, 2014].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also reported that the human-cultured epidermis took and survived on the pressurized skin and nevus after pressurization at 200 MPa [7,9]. Skin consists of the epidermis, which acts as a barrier against infection and water loss, and the dermis, which supports and supplies nutrition to the epidermis.…”
Section: Introductionmentioning
confidence: 99%